Rhytm and Moral Messages in the Qaṣīdah “ʾA min ʾUmmī ʾAwfā Dimnatun Lam Takallamī” by Zuhayr Ibn Abī Sulmā - Danish Algibrani; Nurlinah Nurlinah; Akmaliyah Akmaliyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
his study analyzes the rhythm (wazan) and moral messages in the qasīdah “ʾA min ʾUmmī ʾAwfā Dimnatun Lam Takallamī” by Zuhayr Ibn Abī Sulmā using a descriptive qualitative approach. The data were taken from the poetic text published on the website aldiwan.net, while the data collection technique was conducted through library research and analyzed using the study of ʿarūḍ to determine the type of baḥr and rhythmic variations, namely ziḥāf and ‘illat. The moral messages were then interpreted based on their types and forms. The results show that this qasīdah employs baḥr ṭawīl with a consistent basic pattern, although it frequently undergoes modifications due to the ziḥāf qabḍ. In verse 30, there is also an occurrence of the ‘illat ḥażf. In terms of morality, the most dominant message concerns human relationships with others 30 verses, followed by relationships with oneself 26 verses, and lastly relationships with God 3 verses. Regarding the forms of moral expression, exemplary conduct is the most dominant 30 verses, followed by warnings 21 verses and advice 8 verses, affirming the qasīdah’s character as an ethical reflection on peace, social responsibility, and wisdom in confronting conflict. These findings confirm that the qaṣīdah not only presents the beauty of rhythmic structure within the tradition of ʿarūḍ, but also conveys profound moral messages concerning social relationships, self-control, and human values. This study demonstrates that ʿarūḍ analysis is effective in revealing the relationship between rhythmic patterns and moral meaning in classical Arabic poetry, particularly in identifying the function of zihāf and ʿillat variations as part of both aesthetic and ethical expression in literary texts.